PCDD / FS AND PCBS-WHO IN PLASMA AND BREAST MILK OF RESIDENTS OF THE CHECHEN REPUBLIC - Z. K. Amirova; I. Y. Shahtamirov (Юг России: экология, развитие, 2014)
For the first time polychlorinated dibenzo-para-dioxins, dibenzofurans and toxic biphenyls were found in biological tissues of population in the Chechen Republic. The content in blood was determined within the range of 14.59-61.11 pg TEQ PCDD/F/g lipids and 2.23-48.86 pg TEQ PCB-WHO/g lipids. Dependence on the age of donors was found. The range of values of PCDD/Fs content in breast milk of Chechen women (3.9-14.7 pg/g lipids) corresponds to the data for Russia cities having no active emission sources of chemical production. The levels of PCB-WHO detected in breast milk of women in the Chechen Republic (1.04-3.56 pg/g) are by 5-10 times lower than in Russia at large. This testifies to effect that there have been no active sources of PCB emission for at least 5 recent years.